Education for Sustainable Development and Pedagogical Content Knowledge in Geography: Integration, Evolution or Revolution? First Results of a Qualitative Study of a Seminar Course - Baumann, Stefan; Niebert, Kai (Journal of Geography Education, 2023)
Using the example of teacher training in Geography, this case study uses action research to investigate the question of what a course must include to meet the needs of sustainable development. We surveyed how the perspective of lower secondary teacher training students changes when they deal with Education for Sustainable Development in Geography. Following the introduction of the theory-based conception of the course, we proceed to explore the evaluation of the seminar work. The results shows that students mainly embrace topics of classical Environmental Education and that the transfer of knowledge as a prerequisite for action is of high importance. In order to change the preconceptions, education in general would have to be framed with sustainability.
Keywords: Education for Sustainable Development (ESD), competencies, PCK in Geography, teacher education, action research